Conceptual Design of Single-stage Rocket Using Hybrid Rocket byMeans of Genetic Algorithm. (2015) - Kanazaki, Masahiro; Ariyairt, Atthaphon; Chiba, Kazuhisa; Kitagawa, Koki; Shimada, Toru
Abstract: In this study, a multi-objective genetic algorithm (MOGA) was applied to the multidisciplinary design optimization (MDO) of a hybrid rocket. A swirling-oxidizer-type hybrid rocket engine (HRE) with a single cylindrical grain port was designed. It was considered that this HRE could temporarily stop combustion via oxidizer throttling; this feature is called multi-combustion. The MOGA was applied to solve the multi-objective problem using real-number coding and the Pareto ranking method. In this study, three design problems were considered. First problem was the maximization of the flight altitude and minimization of the gross weight. Second problem was the minimization of the maximum acceleration and minimization of the gross weight. Third problem was the maximization of the duration time over the target flight altitude and minimization of the gross weight. Each objective function was empirically estimated. In addition, this study compared two types of HREs to investigate the emects of the multi-combustion: one type was able to carry out the multi-combustion, and the other was not. Many non-dominated solutions were obtained using the MOGA, and a trade-off was observed between the two objective functions. To understand the design problem, the MOGA results were visualized using a parallel coordinate plot (PCP).